Perceptions of the EU in Eastern Europe and Sub-Saharan Africa
XII, 226 p.
Keywords: This collection examines how the EU is seen in the two regions that are at the centre of its geopolitical interest. Focusing on Eastern Europe and sub-Saharan Africa, it provides a critical assessment of how their external perceptions relate to EU policy towards them.